Biophysical effects of an old tundra fire in the Brooks Range Foothills of Northern Alaska, U.S.A - Miller, Eric A.; Baughman, Carson A.; Jones, Benjamin M.; Jandt, Randi R. (Polar science, 2024)
Our understanding of tundra fire effects in Northern Alaska is limited because fires have been relatively rare. We sampled a 70+ year-old burn visible in a 1948 aerial photograph for vegetation composition and structure, soil attributes, terrain rugosity, and thermokarst pit density. Between 1948 and 2017 the burn initially became wetter as ice wedges melted but then drained and dried as the troughs became hydrologically connected. The reference tundra has become wetter over the last few decades and appears to be lagging through a similar sequence. The burn averaged 2.5 °C warmer than the reference tundra at 30 cm depth. Thinning of organic soil following fire appears to dramatically accelerate the background degradation of ground-ice features in response to climate change and promotes a plant community that is distinct in terms of taxa and structure, dominated by tall willows and other competitive, rather than cold-tolerant, species. The cover of sedges and mosses is low while that of willows and grass is high relative to the reference tundra. The changes in plant community composition and structure, increasing ground temperature, and thermokarst lead us to expect the observed biophysical changes to the tundra will persist centuries into the future. •An old tundra burn was found in a 1948 aerial photograph in northern Alaska.•Fire resulted in melted ground-ice, thermokarst, and conspicuously tall willows.•The adjacent unburned tundra also shows signs of thermokarst related to climate change.•There was a shift from cold-tolerant to competitive plants within the burn.•Ground temperature continues to warm relative to the unburned tundra.